Citizen satisfaction with public services in Peru: Regional gaps in citizen perceptions of public service provision - Miluska Odely Rodriguez-Saavedra; Iván Cuentas Galindo; Luis Miguel Campos Ascuña; Antonio Víctor Morales Gonzales; José Luis Chavez Cuarite; Adolfo Erick Donayre Sarolli; Erick Alexander Donayre Prado; Robinson Bernardino Almanza Cabe; Ruben Washington Arguedas Catasi (PLoS ONE, 2026)
Citizen satisfaction with public services is a fundamental indicator of government effectiveness and democratic legitimacy in Latin America. However, there is little empirical evidence on regional gaps in countries with high territorial heterogeneity such as Peru. The objective of this study was to determine the differences in levels of citizen satisfaction with public services between the country’s coastal, mountain, and jungle regions. A secondary analysis was conducted of the 2024 National Household Survey, corresponding to the Governance, Democracy, and Transparency Module (n = 33,691), evaluating 21 public services using the Citizen Satisfaction Index. Student’s t-tests were applied for comparisons between urban and rural areas, one-factor ANOVA with Bonferroni post-hoc tests for comparisons between geographic domains, and principal component analysis to explore the dimensional structure. The results revealed statistically significant differences between the eight geographic domains (F = 89.57, p < .001, η² = .022); although this effect size is small, indicating that geographic domain accounts for 2.2% of the variance in satisfaction, the patterns are consistent and policy-relevant. The North Coast (M = 3.09) and Amazon (M = 3.13) showed the lowest satisfaction rates, while the Southern Highlands (M = 3.29) even surpassed Metropolitan Lima. Social programs (51.9%) and the Public Prosecutor’s Office (56.4%) obtained the lowest national satisfaction ratings, with the largest regional gaps. Rural areas reported higher satisfaction with public transportation (+7.0%) and public education (+3.5%) than urban areas. A four-dimensional factor structure was identified that explains 46.7% of the variance. It is concluded that territorial gaps are consistent with structural differences in regional institutional capacity, requiring territorially differentiated public policies to reduce inequalities in the provision of state services.